Pengaruh Digital Literacy terhadap Kemampuan Reading Comprehension Anak Usia Sekolah: A Systematic Literature Review - Sudarman Sudarman; Roy Romey Daulas Mangunsong (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Rapid technological development has transformed reading instruction among school-age children. Digital literacy has become an essential twenty-first century competency because it enables learners to access, understand, evaluate, and utilize information through digital media. Previous studies have reported positive effects of digital media on reading comprehension; however, findings remain varied. Objectives: To analyze and synthesize evidence regarding the influence of digital literacy on reading comprehension among school-age children. Methods: This study employed a Systematic Literature Review (SLR) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 framework. Articles were retrieved from Google Scholar, Scopus, ERIC, ScienceDirect, and DOAJ databases. Eligible studies were published between 2020 and 2026 and focused on digital literacy and reading comprehension among school-age children. Twenty-five studies met the inclusion criteria and were synthesized narratively. Results: The findings indicate that digital literacy positively influences reading comprehension skills. Positive outcomes include improved understanding of texts, increased reading motivation and engagement, enhanced learning participation, and stronger critical thinking skills. Commonly used digital media included digital storybooks, digital flipbooks, Let’s Read applications, BukuAku, interactive e-books, and digital audiovisual learning media. Conclusion: Digital literacy contributes positively to reading comprehension among school-age children. Its effectiveness is influenced by digital media quality, teacher competence, learning environment support, and students’ ability to manage digital distractions. Keywords: Digital literacy, Reading Comprehension, School-Age Children, Digital Learning, Reading Literacy.